Pola Komunikasi Keluarga dalam Mengimplementasikan Ajaran Wacika Parisudha - Puspa, Ida Ayu Tary; Paramita, Ni Luh Mas; Dewi, Anak Agung Nia Listiana (Institut Hindu Dharma Denpasar, 2020)
Family is the inner bond between father, mother and child. In living, parents have a role in educating and raising their children. In order to establish a harmonious relationship between them, communication between father and mother, parent and child is needed and vice versa. Today, due to the influence of globalization, children imitate friends in social circles, as well as from social media, so that sometimes children do the wrong words. It is time for the role of parents in educating children to teach the right way to say according to the teachings of Wacika Parisuda. So that children do not ujar Ahala, ujar Apergas, ujar Micuna, and ujar Mitya. Thus, by carrying out Wacika Parisuda, children can become suputra children.